Nutritional associations with decelerated epigenetic aging: vegan diet in a Dutch population - Georges E. Janssens; Jenny van Dongen; Lannie Ligthart; Eco J. C. de Geus; Gajja S. Salomons (Clinical Epigenetics)
Abstract Background The 2021 Aging Report of the European Union projected significant increases in healthcare costs, with some member states expecting up to a 60% rise over the next 50 years, primarily due to an aging population and related diseases. Interventions targeting aging have been proposed to reduce this burden by extending healthspan. Recent evidence suggests that vegan diets may slow the aging process. Results Using data from the Netherlands Twin Register (n = 22,124), dietary habits of meat eaters (n = 21,614), pescetarians (n = 294), vegetarians (n = 194), and vegans (n = 22) were examined, which were collected in a 2014–2016 survey period. Health parameters such as BMI, waist circumference, and insulin sensitivity showed improved health with more plant-based diets, though results were not adjusted for confounders. Epigenetic age was assessed using the Hannum, Horvath, PhenoAge, GrimAge, and Dunedin Pace of Aging clocks for 3049 participants with DNA methylation (DNAme) data from a 2004–2011 sample collection period and were compared to calendar age from the time of blood draw. Although discordant twin pairs with and without vegan diets (n = 3) were too few for statistical significance, their results suggested a potential benefit of veganism. In the subpopulation with complete data on DNA methylation, dietary habits, and covariates (n = 1198), veganism was significantly associated with lower epigenetic aging scores on the Hannum and Horvath clocks, even after adjusting for confounders (age, sex, smoking, education, physical activity, BMI, and alcohol use). Analysis of individual covariates in the model found that higher education, physical activity, being female, and non-smoking were associated with reduced epigenetic age, while higher BMI was linked to increased epigenetic age; however, since these parameters were used with the primary purpose of accounting for confounders, caution should be used in interpreting these results. Finally, dietary analysis showed that abstaining from pork was associated with lower biological ages (Dunedin Pace of Aging), whereas abstaining from poultry was linked to higher biological ages (PhenoAge, Dunedin Pace of Aging). Conclusions Although with a small sample size and a large time gap between nutritional survey collection and blood collection for participant’s epigenetic ages, these findings suggest that dietary choices, particularly plant-based diets, may influence epigenetic aging. The results highlight the potential of veganism to reduce epigenetic age and underscore the importance of further research to clarify the relationship between diet and aging. Larger cohorts and clinical trials would be necessary to gain more certainty on our initial findings.